GADIMATH: Gamified Discrete Mathematics - Jan Mark S. Garcia; Reymund L. Sabay (Philippine Social Science Journal, 2020)
GADIMATH: Gamified Discrete Mathematics is an interactive two-dimensional mobile-based application in discrete mathematics working on the Android program. This application would work as an additional tool to strengthen the students' training in discrete mathematics. It would benefit students to observe particular rules, accomplish goals, and resolve problems. Upon using the application, students would experience enjoyment, interaction, and motivation while learning takes place. The problems and difficulties that the students encountered towards mastering learning competencies in mathematics are the instructions, school adjustments, and over-extended schedules. With all these difficulties and struggles, the proponent produces the GADIMATH's main features: user-friendliness, infotainment, authenticity, interactivity, learning support, portability, and changing environment. GADIMATH has seven functions: choose avatar, gameplay, backpack, shop, settings, help, and about that are merged to form a final and impeccable product.